Adsorpsi Krom Total Pada Limbah Batik Menggunakan Sampah Plastik Sebagai Karbon Aktif - Elizabeth Britney Calista; Nomeritae; I Made Kamiana (Jurnal Serambi Engineering, 2024)
The Katingan Hilir District of Katingan Regency, Central Kalimantan Province, is one of the areas experiencing the consequences of flood disasters. This research aims to analyse the flood-affected areas using the GIS method, integrating the Analytic Hierarchy Process (AHP) method in order to analyse the impact and influencing factors on flood events. This is one of the decision support system methods of Multiple Attribute Decision Making (MADM), which is included in the technical category. MCDM (Multi-criteria decision making) was developed by Thomas L. Saaty with the objective of identifying the most optimal and feasible problem-solving/alternative results through systematic evaluation procedures [1]. The parameters obtained based on the ranking of their influence on flood vulnerability are as follows: The following parameters were identified as influencing flood vulnerability: rainfall, distance from the river, slope, elevation, soil type and land cover. The results of the map overlay indicated that a total area of 403.11 km2 (67.1%) exhibited a low level of flood vulnerability, 146.93 km2 (24.5%) exhibited a medium level of flood vulnerability, and 50.34 km2 (8.4%) exhibited a high level of flood vulnerability. The area and percentage values indicate that the study location is a dominant area with a low level of flood vulnerability, yet it has a high category of flood-prone percentage approaching 10% of the total administrative area of the sub-district.